A Universal Seeding Strategy to Synthesize Single Atom Catalysts on 2D Materials for Electrocatalytic Applications. (14th November 2019) - Zhao, Shiyong; Chen, Guangxu; Zhou, Guangmin; Yin, Li‐Chang; Veder, Jean‐Pierre; Johannessen, Bernt; Saunders, Martin; Yang, Shi‐Ze; De Marco, Roland; Liu, Chang; Jiang, San Ping
Abstract: Single‐atom catalysts (SACs) are attracting significant attention due to their exceptional catalytic performance and stability. However, the controllable, scalable, and efficient synthesis of SACs remains a significant challenge. Herein, a new and versatile seeding approach is reported to synthesize SACs supported on different 2D materials such as graphene, boron nitride (BN), and molybdenum disulfide (MoS2 ). This method is demonstrated on the synthesis of Ni, Co, Fe, Cu, Ag, Pd single atoms as well as binary atoms of Ni and Cu codoped on 2D support materials with the mass loading of single atoms in the range of 2.8–7.9 wt%. In particular, the applicability of the new seeding strategy in electrocatalysis is demonstrate on nickel SACs supported on graphene oxide (SANi‐GO), exhibiting excellent catalytic performance for electrochemical CO2 reduction reaction with a turnover frequency of 325.9 h −1 at a low overpotential of 0.63 V and high selectivity of 96.5% for CO production. The facile, controllable, and scalable nature of this approach in the synthesis of SACs is expected to open new research avenues for the practical applications of SACs. Abstract : A facile, controllable, and scalable method is developed for the fabrication of single‐atom catalysts (SACs) on various 2D material supports with high loading and activities via a new seeding approach, significantly accelerating the practical application of SACs for the areas of electrocatalysis and catalysis.